Report on field survey of sheep in Ethiopia from August 8th till August 18th, 1970, in the provinces of Wollo, Tigre and Harar - Oppenheimer, B. (1970)
Village and market survey was conducted to check quantities, varieties, weight and prices of sheep in Harar, Tigray and wollo provinces. In Harar province, Black Head sheep type is found. Adults (mainly 2 years old) weighed between 10-12 kg. In addition, information was obtained from market assessment and meeting with village heads about some of production and reproduction performances of the animals, husbandry and selling prices at markets in Jijiga, Asbe Teferi, Miesso, Harar, DireDawa and Matahara. Similar survey was also conducted in Tigre and wollo provinces. There, highland sheep with variety coat colour types (mostly brown in Tigre and black in Wollo) were noted from mountain areas and Danakil sheep brought from Danakil area. Adult highland sheep weighed between 15-20 kg and had fleece about 5-8 cm long. Danakil sheep weighed 15-30 kg with no wool. Furthermore, information on market selling prices, seasonal variation of feed available and breeding, reproductive performance and diseases was included from data from agricultural offices. Inaddition, some of linear body measurements, body weight, coat colour etc. Management methods and production potential and feed assessment was made with respect to each of the four breeds of sheep. Finally methods of fattening system presented with schematic layout. Recommended caring and utilization of feed, materials needed, possibilities of improvement and cost of sheep fattening and dispatch system are indicated.